2014
DOI: 10.1063/1.4863098
|View full text |Cite
|
Sign up to set email alerts
|

Online tuning of impedance matching circuit for long pulse inductively coupled plasma source operation—An alternate approach

Abstract: Impedance matching circuit between RF generator and the plasma load, placed between them determines the RF power transfer from RF generator to the plasma load. The impedance of plasma load depends on the plasma parameters through skin depth and plasma conductivity or resistivity. Therefore, for long pulse operation of ICPs, particularly for high power (~ 100kW or more) where plasma load condition may vary due to different reasons (e.g. pressure, power, thermal etc.), online tuning of impedance matching circuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…The transformed plasma resistance has been calculated to 1.8 Ω from the parallel capacitance which is necessary to achieve 50 Ω at the output of the amplifier or SWR=1 respectively. This value is consistent with the results achieved by transformer model calculations for inductive discharge in [12].…”
Section: Matching With Different Transformers and Without Transformersupporting
confidence: 81%
“…The transformed plasma resistance has been calculated to 1.8 Ω from the parallel capacitance which is necessary to achieve 50 Ω at the output of the amplifier or SWR=1 respectively. This value is consistent with the results achieved by transformer model calculations for inductive discharge in [12].…”
Section: Matching With Different Transformers and Without Transformersupporting
confidence: 81%
“…Therefore, it is clearly understood that major contribution of error comes from R p . The value of R p is estimated in the process of impedance matching calculation [15] and it is experimentally observed that ~ 70% matching is only possible in reality, as reflected in the experimental cos values in the fig.8 of reference 15. Remaining ~ 30% can be considered as the uncertainty of the R p estimation due to the simplified assumption based on solenoid approximation of the RF coil.…”
Section: Figurementioning
confidence: 99%
“…The term L mp is due to the discharge current path and is inductively coupled to the primary coil through mutual inductance M . The figures 3b -3c [15] depict only the coupling phenomena between the coil antenna and the plasma, based on transformer model [15] and do not include the electrical parameters of the impedance matching circuit.…”
Section: Plasma Resistance Of An Icp Using Transformer Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the above mechanism, i.e., the dependencies of Q with the separation between the primary antenna and the helical coil, we have modelled the resonator along with the primary antenna as air core transformer. 13,14 The primary antenna, electrically connected with the RF source, is considered to be transformer primary coil and the helical coil as the secondary coil (Fig. 4(a)).…”
mentioning
confidence: 99%